Methanol extract of Muntingia calabura leaves attenuates CCl4-induced liver injury: possible synergistic action of flavonoids and volatile bioactive compounds on endogenous defence system. (1st January 2019) - Zakaria, Zainul Amiruddin; Mahmood, Nur Diyana; Omar, Maizatul Hasyima; Taher, Muhammad; Basir, Rusliza
Abstract: Context: Muntingia calabura L. (Muntingiaceae) exerts antioxidant and anti-inflammatory activities, thus, it might be a good hepatoprotective agent. Objective: This study investigates the effect of methanol extract of M. calabura leaves (MMCL) on hepatic antioxidant and anti-inflammatory activities in CCl4 -induced hepatotoxic rat. Materials and methods: Sprague Dawley rats ( n  = 6) were treated (p.o.) with 10% DMSO (Groups 1 and 2), 50 mg/kg N -acetylcysteine (Group 3) or, 50, 250, or 500 mg/kg MMCL (Groups 4–6) for 7 consecutive days followed by pretreatment (i.p.) with vehicle (Group 1) or 50% CCl4 in olive oil (v/v) (Groups 2–6) on day 7th. Plasma liver enzymes and hepatic antioxidant enzymes and pro-inflammatory cytokines concentrations were measured while liver histopathology was examined. Results: MMCL, at 500 mg/kg, significantly ( p  < 0.05) ameliorated CCl4 -induced hepatotoxicity by decreasing the plasma level of alanine transaminase (429.1 versus 168.7 U/L) and aspartate transaminase (513.8 versus 438.1 U/L) as well as the tissue level of nitric oxide (62.7 versus 24.1 nmol/g tissue). At 50, 250, or 500 mg/kg, MMCL significantly ( p  < 0.05) reduced the tumour necrosis factor α (87.8 versus 32.7 pg/mg tissue), interleukin-1β (1474.4 versus 618.3 pg/mg tissue), and interleukin-6 (136.7 versus 30.8 pg/mg tissue) while increased the liver catalase (92.1 versus 114.4 U/g tissue) and superoxide dismutase (3.4 versus 5.5 U/g tissue). Additionally, qualitative phytochemicals analysis showed that MMCL contained gallic acid, ferulic acid, quercetin, and genistein. Discussion and conclusions: MMCL ability to attenuate CCl4 -induced hepatotoxicity could be helpful in the development of hepatoprotective agents with fewer side effects.